Treatment Options for Plantar Fasciitis: Surgical Release vs. Conservative Therapy - Wojtach, Klaudia; Szałajska, Julia; Czyżewski, Filip; Wiak, Iga; Banyś, Filip; Łukawski, Artur; Bochen, Konrad; Pasierb, Karolina; Jasiński, Filip; Dudek, Stanisław (Quality in Sport, 2024)
Introduction Plantar fasciitis is one of the most common reasons for visits to orthopedic clinics. This tendinopathy can cause medial heel pain, stiffness, and tenderness on the plantar surface of the foot. Both conservative and surgical methods are employed in its treatment. Aim The aim of this study is to evaluate selected conservative treatment methods, such as stretching, the use of orthotic insoles, splints, injections, extracorporeal shockwave therapy, and taping, as well as surgical treatment options. The study presents a comparison of these methods in terms of their effectiveness, advantages, and disadvantages. State of Knowledge The plantar fascia is a stiff, connective tissue structure extending along the plantar surface of the foot. Biomechanical load on the fascia, which supports the medial longitudinal arch, can lead to degenerative changes that underlie plantar fasciitis. Symptoms include pain, particularly in the mornings and late evenings, which intensifies with palpation of the heel area. Summary (Conclusions) Conservative treatments for plantar fasciitis are effective in 90% of patients. There are no studies that conclusively demonstrate the superiority of one treatment method over another. Thus, the choice of therapy should be tailored to the patient’s lifestyle, activity level, and financial capability. Surgical intervention is necessary in cases of chronic plantar fasciitis which remains resistant to conservative treatments.